Gramsci Dictionary - Dizionario gramsciano: Tanja - Durante, Lea (International Gramsci Journal, 2025)
This is an English translation of the entry in the Dizionario gramsciano (Roma, Carocci 2009) on “Tania” (here “Tanja” or in full “Tat’jana”) Schucht, Gramsci’s wife’s sister. Tanja played a well-known self-denying role for Gramsci; she was a complex ‘you’ for him, conveying moral, material and emotional aid, and providing an essential link with the outside world. This latter included his wife Julija (Giulia), living in Moscow, with many letters to Tanja also meant to be read by Julija. Further to this, there is a more latent side to the relationship between the two of them. Gramsci was often critical of her, and to her letters of solicitude to his demands and her self-denial, he often replied in a pressing fashion, adopting a patronizing and sometimes authoritarian tone and not undertaking personal initiative. When she undertook some well-meaning action, somewhat typical, in a letter of his dating to 1932, is his charge of ‘irresponsible dilettantism’ on her part. At the same time his bonds of affection with her were very close, though subject to the aspect of being functional to his requirements. Judged from the outside it was a relationship not of equals but of ‘man-intellectual’ against ‘woman-child’.